Impact of Private Foreign Investment on Economic Growth: A Study of Nigeria (1999-2021) - John , Davies; Smith, Robert; Williams, Laura (Ayden International Journal of Banking, Finance and Technology, 2024)
To facilitate economic growth, there must be an adequate level of savings and investments, and one avenue to improve the level of savings and investments is to attract private foreign capital. Therefore, this study assessed the effect of private foreign capital on economic growth in Nigeria from 1999-2021. The study proposed a model of economic growth using private foreign capital variables such as foreign direct investment (FDI), foreign portfolio investment (FPI), and remittances as predictors. The data were subjected to unit root tests and were found to be stationary in mixed order at levels and first difference justifying the choice of the Autoregressive Distributed Lag approach for data analyses. The result of the ARDL test revealed that FDI is significant and positively influences economic growth (β = 2.84, p<0.05). Likewise, remittances are significant but have a negative contribution to economic growth (β = -0.71 , p<0.05). FPI was found to not affect economic growth in Nigeria (β = 0.02, ns) in the longrun. Also, the estimated coefficients of the shortrun relationship for the model revealed that FDI and remittances are significant in impacting economic growth with FDI contributing positively (β = 2.70, p<0.05) and remittances contributing negatively (β = -0.68 , p<0.05). FPI still failed to influence economic growth in Nigeria (β = -0.33 , ns). Therefore, the study concludes that foreign direct investment and remittances are significant predictors of economic growth. The study recommended that a stable and predictable policy environment needs to be in place to build foreign investors’ confidence.